1984
DOI: 10.1161/01.cir.70.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic restrictive cardiomyopathy.

Abstract: This report details the clinical, hemodynamic, and morphologic data from four patients 59 to 77 years old (mean 66) with a primary restrictive cardiomyopathy. All patients had symptoms of congestive heart failure, jugular venous distention, and murmurs of mitral and tricuspid regurgitation. Four patients required pacemakers, three for the brady-tachy syndrome and one for complete heart block. Chest x-ray demonstrated cardiomegaly in all four patients and pulmonary congestion and/or pleural effusions in three. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(18 citation statements)
references
References 13 publications
0
17
1
Order By: Relevance
“…Little is known about the prognosis of true idiopathic RCM, because most published reports have included patients with known chronic hypertension, coronary artery disease, and even ventricular enlargement and hypertrophy, 8,9,13 and as a result, their outcome was substantially different from that observed in this study. In this study, we have attempted, to the best of our ability, to exclude patients with a possible secondary form of RCM by adhering to very strict inclusion and exclusion criteria.…”
Section: Outcomecontrasting
confidence: 65%
See 3 more Smart Citations
“…Little is known about the prognosis of true idiopathic RCM, because most published reports have included patients with known chronic hypertension, coronary artery disease, and even ventricular enlargement and hypertrophy, 8,9,13 and as a result, their outcome was substantially different from that observed in this study. In this study, we have attempted, to the best of our ability, to exclude patients with a possible secondary form of RCM by adhering to very strict inclusion and exclusion criteria.…”
Section: Outcomecontrasting
confidence: 65%
“…5,6 Idiopathic RCM has been reported in small series of 9, 4, and 5 patients. 8,9,13 However, these series included patients with hypertension, coronary disease, neurofibromatosis, and echocardiographic or autopsy findings of ventricular hypertrophy or enlargement. Our study, to the best of our knowledge, has excluded patients in whom RCM could have been secondary to other disease states.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[8][9][10][11][12][13][14] The interstial fibrosis can vary from mild to severe. In a large series of biopsies from 37 patients with IRC, Ammash et al demonstrated interstitial fibrosis that was predominantly pericellular in 81%.…”
Section: Morphological Spectrum Of Idiopathic Restrictive Cardiomyopathymentioning
confidence: 99%